1994
DOI: 10.1111/j.1365-294x.1994.tb00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of populations of threatened snake species using RAPD markers

Abstract: Snakes are a particularly threatened vertebrate taxon, with distributions of many species and populations becoming increasingly fragmented. At present, little is known about the degree of genetic differentiation that exists between isolated populations even though such information may be critical to their survival and conservation. As an example of how recently developed RAPD genetic markers can be used in conservation genetics, we present preliminary results from a study which used these DNA‐based markers to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
1
3

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 22 publications
4
30
1
3
Order By: Relevance
“…It should be noted, however, that the small number of loci we used may limit the interpretation of our results. Previous population genetic studies of snakes using allozymes, randomly amplified polymorphic DNA (RAPDs), or mtDNA loci generally revealed little to no variation among intraspecific populations (e.g., Sattler and Guttman 1976;Gartside et al 1977;Lawson 1987;Dessauer et al 1987;Rose and Selcer 1989;Gibbs et al 1994; Thompson and Crother 1998). A growing number of microsatellite studies, however, have indicated comparable levels of diversity and differentiation as detected here (Table 3).…”
Section: Discussionsupporting
confidence: 56%
“…It should be noted, however, that the small number of loci we used may limit the interpretation of our results. Previous population genetic studies of snakes using allozymes, randomly amplified polymorphic DNA (RAPDs), or mtDNA loci generally revealed little to no variation among intraspecific populations (e.g., Sattler and Guttman 1976;Gartside et al 1977;Lawson 1987;Dessauer et al 1987;Rose and Selcer 1989;Gibbs et al 1994; Thompson and Crother 1998). A growing number of microsatellite studies, however, have indicated comparable levels of diversity and differentiation as detected here (Table 3).…”
Section: Discussionsupporting
confidence: 56%
“…However, the timber rattlesnake (Crotalus horridus) displayed a high level of phylopatry, with genetic distances between hibernacula being larger and significant in 50% of the comparisons (Villarreal et al 1996). Within the massasauga rattlesnake (Sistrurus c. catenatus), microsatellites markers revealed a huge differentiation between populations (Gibbs et al 1997), whereas RAPD analyses did not show any structure between the same populations (Gibbs et al 1994; see also Gibbs et al 1997 for the comparison). Also based on RAPD, Jäggi et al (2000) demonstrated a low genetic differentiation within asp viper (V. aspis) populations in the Jura Mountains.…”
Section: Introductionmentioning
confidence: 92%
“…[4,5]), and identification of differences among strains, subspecies, or species (see e.g., ref. [6][7][8]). The methods used for such purposes include randomly amplified polymorphic DNA (RAPD) [9]; arbitrarily primed PCR (AP-PCR) [10]; DNA amplification fingerprinting (DAF) [11]; multiple arbitrary amplicon profiling (MAAP) [12]; amplified fragment length polymorphism (AFLP) [13]; representational difference analysis (RDA) [14,15]; and suppressive subtractive hybridization (SSH) [16,17].…”
Section: Introductionmentioning
confidence: 97%